Cross-sectional assessment reveals high diabetes prevalence among newly-diagnosed tuberculosis cases - Blanca I Restrepo; Aulasa J Camerlin; Mohammad H Rahbar; Weiwei Wang; Mary A Restrepo; Izelda Zarate; Francisco Mora-Guzmán; Jesus G Crespo-Solis; Jessica Briggs; Joseph B McCormick; Susan P Fisher-Hoch (The World Health Organization, 2011)
OBJECTIVE: To estimate the contribution of clinically-confirmed diabetes mellitus to tuberculosis (TB) rates in communities where both diseases are prevalent as a way to identify opportunities for TB prevention among diabetic patients. METHODS: This is a prospective study in which TB patients > 20 years old at TB clinics in the Texas-Mexico border were tested for diabetes. The risk of tuberculosis attributable to diabetes was estimated from statistics for the corresponding adult population. FINDINGS: The prevalence of diabetes among TB patients was 39% in Texas and 36% in Mexico. Diabetes contributed 25% of the TB cases studied, whereas human immunodeficiency virus (HIV) infection contributed 5% or fewer. Among TB patients, fewer Mexicans than Texans were aware that they had diabetes before this study (4% and 19%, respectively). Men were also less frequently aware than women that they had diabetes (P = 0.03). Patients who knew that they had diabetes before the study had an 8-year history of the disease, on average, before being diagnosed with TB. CONCLUSION: Patients with diabetes are at higher risk of contracting TB than non-diabetic patients. Integrating TB and diabetes control programmes worldwide would facilitate TB prevention among diabetes patients and increase the number of diabetics who learn of their condition, particularly among males. Such a strategy would lead to earlier case detection and improve the management of both TB and diabetes.